Long-Term Employment Effects of the Minimum Wage in Germany: New Data and Estimators - Marco Caliendo; Nico Pestel; Rebecca Olthaus (Institute of Labor Economics (IZA), 2024)
We investigate the long-term effects of the introduction of the German minimum wage in 2015 and its subsequent increases on regional employment. Using comprehensive survey data, we are able to measure the regional bite of the minimum wage in 2014, just before its introduction, as well as in 2018, before it was raised substantially in several steps. The introduction mainly affected the labour market in East Germany, while the minimum wage increases increasingly affected low-wage regions in West Germany, with about one third of regions changing their (binary) treatment status between 2014 and 2018. We use different specifications and extensions of the canonical difference-in-differences approach, as well as a set of new estimators that allow unbiased effect estimation with a staggered treatment adoption and heterogeneous treatment effects. Our results show a small negative effect on total dependent employment of 0.5%, driven by a significant reduction in marginal employment of 2.4%. The extended specifications suggest additional effects of the minimum wage increases, as well as stronger negative effects for those regions that were strongly affected by the minimum wage in both periods.
Keywords: J23; J31; J38; 330; minimum wage; employment; regional bite